Analysis of the Role of Financial Statements in Creative Industry-Based MSMEs - Budi Dharma; Laila Fitria; Chadisa Rizky Ananda (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
MSME is one of the most important sectors in Indonesia which encourages economic development, increases economic operational capital. The existence of MSMEs is able to absorb more workers and encourage increased social welfare and reduce unemployment in Indonesia. One aspect that plays an important role in the development and running of an MSME is the quality of financial reports. PSAK No. 1 concerning Presentation of Financial Statements explains that financial reports are a structured presentation of the financial position and financial performance of a particular business entity. This study aims to analyze the role of financial reports on creative industry-based SMEs. The method used in this study is a qualitative research method of library research which focuses on observing a condition or social phenomenon which is then analyzed to describe the subject matter studied. The results of the study show that financial reports provide information on financial position, achievements from MSME business results, empowering and developing MSME. In addition, financial reports encourage an increase in MSME income, provide an overview of the total assets, liabilities and capital of a bank for a certain period of time and provide information on entity cash flows for making economic decisions on an MSME.